Peningkatan Keterampilan Menulis Teks Eksplanasi melalui Metode Pembelajaran Mind-Mapping di SMP Negeri 1 Sokaraja - Bivit Anggoro Prasetyo Nugroho; Memet Sudaryanto; Melia Istiani (Medan Resource Center, 2023)
The purpose of this study was to improve the learning outcomes of class VIII students in writing explanatory texts through the Mind-Mapping learning method. Learning outcomes can be achieved in accordance with learning objectives through the role of educators in developing interactive learning tools. The Mind-Mapping learning method is an interactive method that can improve students' explanatory text writing skills. The application of the Mind-Mapping method at SMP Negeri 1 Sokaraja through classroom action research includes four steps, namely: (1) planning; (2) action; (3) observation; and (4) reflection. The results of this study indicate an increase in student learning outcomes in the skills of writing explanatory texts in pre-cycle, cycle I, and cycle II. The 8 aspects of the assessment have increased from the pre-cycle stage to cycle II. The average ability of students to write explanatory texts in pre-cycle was 5.5, cycle I was 7.12 and cycle II was 8.62. The application of the Mind-Mapping learning method can be an alternative in improving the ability to write explanatory texts in class VIII students.